Tacrine(10)-Hupyridone Prevents Post-operative Cognitive Dysfunction via the Activation of BDNF Pathway and the Inhibition of AChE in Aged Mice - Chen, Huixin; Wu, Xiang; Gu, Xinmei; Zhou, Yiying; Ye, Luying; Zhang, Ke; Pan, Hanbo; Wang, Jialing; Wei, Hua; Zhu, Binbin; Naman, C. Benjamin; Mak, Shinghung; et al. (Frontiers in Cellular Neuroscience, 2018)
Post-operative cognitive dysfunction (POCD) could cause short-term or long-term cognitive disruption lasting weeks or months after anesthesia and surgery in elderly. However, no effective treatment of POCD is currently available. Previous studies indicated that the enhancement of brain-derived neurotrophic factor (BDNF) expression, and the elevation the cholinergic system, might be effective to prevent POCD. In this study, we have discovered that tacrine(10)-hupyridone (A10E), a novel acetylcholinesterase (AChE) inhibitor derived from tacrine and huperzine A, could prevent surgery-induced short-term and long-term impairments of recognition and spatial cognition, as evidenced by the novel object recognition test and Morris water maze tests, in aged mice. Moreover, A10E significantly increased the expression of BDNF, and activated the downstream Akt and extracellular regulated kinase (ERK) signaling in the surgery-treated mice. Furthermore, A10E substantially enhanced choline acetyltransferase (ChAT)-positive area in the hippocampus regions of surgery-treated mice, indicating that A10E could prevent surgery-induced dysfunction of cholinergic system, possibly via increasing the synthesis of acetylcholine and the inhibition of AChE. In conclusion, our results suggested that A10E might prevent POCD via the activation of BDNF pathway and the inhibition of AChE, concurrently, in aged mice. These findings also provided a support that A10E might be developed as a potential drug lead for POCD.